Splenic Artery Embolization for the Treatment of Gastric Variceal Bleeding Secondary to Splenic Vein Thrombosis Complicated by Necrotizing Pancreatitis: Report of a Case - Hee Joon Kim; Eun Kyu Park; Young Hoe Hur; Yang Seok Koh; Chol Kyoon Cho (Case Reports in Medicine)
Splenic vein thrombosis is a relatively common finding in pancreatitis. Gastric variceal bleeding is a life-threatening complication of splenic vein thrombosis, resulting from increased blood flow to short gastric vein. Traditionally, splenectomy is considered the treatment of choice. However, surgery in necrotizing pancreatitis is dangerous, because of severe inflammation, adhesion, and bleeding tendency. In the Warshaw operation, gastric variceal bleeding is rare, even though splenic vein is resected. Because the splenic artery is also resected, blood flow to short gastric vein is not increased problematically. Herein, we report a case of gastric variceal bleeding secondary to splenic vein thrombosis complicated by necrotizing pancreatitis successfully treated with splenic artery embolization. Splenic artery embolization could be the best treatment option for gastric variceal bleeding when splenectomy is difficult such as in case associated with severe acute pancreatitis or associated with severe adhesion or in patients with high operation risk.